First record of the introduced freshwater leech Helobdella europaea Kutschera 1987 in Portugal - S. Ferreira; D. Oliveira; L. P. da Silva; A. Utevsky; S. Utevsky (Arxius de Miscel-lània Zoològica)
Primer registre de la sangonera exòtica d'aigua dolça Helobdella europaea Kutschera 1987 a Portugal (Hirudinea, Glossiphoniidae)